Interactions between copy number and expression level of genes involved in fluconazole resistance in Candida glabrata - Abbes, Salma; Sellami, Hayet; Michel-Nguyen, Annie; Ayadi, Ali; Ranque, Stéphane (Frontiers in Cellular and Infection Microbiology, 2013)
Objectives. This study aimed to elucidate the relative involvement of drug resistance gene copy number and overexpression in fluconazole resistance in clinical C. glabrata isolates using a population-based approach. Methods. Fluconazole resistance levels were quantified using the minimal inhibitory concentration (MIC) via Etest method. Both gene expression levels and gene copy number of CgCDR1, CgPDH1, CgERG11 and CgSNQ2 were assessed via quantitative real-time PCR. The influence of the main effects and first-level interactions of both the expression level and copy number of these genes on fluconazole resistance levels were analyzed using a multivariate statistical model. Results. Forty-three C. glabrata isolates were collected from 30 patients during in a hospital survey. In the multivariate analysis, C. glabrata fluconazole MICs were independently increased by CgSNQ2 overexpression (p